Pengaruh Suhu Terhadap Karakteristik Pengeringan Rebung Bambu Tabah (Giganthochloa nigrociliata Kurz) - Lestari, Angelia Puji; Kencana, P.K. Diah; Wijaya, I Made Anom S. (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 4 No 1 (2016): Maret, 2016)
Bamboo tabah shoots is a product with high level of water which is 91% and easily damaged after harvested, so the advanced handling was need to keep the quality and storage period. One method is by drying. The purpose of this research is to study the effects of temperature the drying characteristics of bamboo tabah shoots. According from this research, bamboo tabah shoots was dry by oven and used 5 points of temperatures as the way of treatment. This research was using data from weighing the mass of material within drying process to obtain decreasing of moisture content and drying rate in bamboo tabah shoots. The temperature of drying that used in this research were 50?C, 55?C, 60?C, 65?C, and 70?C. From this research known that the drying temperatures have the effects to the result of the drying characteristics, but have no effect to the physical characteristics of drying bamboo tabah shoots. The lowest drying rate that found from the objects that was dried using 50?C is 31,82%db/hour which was dried for 32 hour with the final water level 9,38%wb and the highest dried rate found from the object that was dried using 70?C is 72,04%db/hour which was dried for 18 hour with the final water level 9,74%wb. The drying rate increased by the increase of temperature
Keywords: Drying bamboo shoots, drying, drying rate, temperature of drying